The role of Malay traditional house and Rumah Gadang as homestays / Rohaslinda Ramele and Jonny Wongso - Ramele, Rohaslinda; Wongso, Jonny (Universiti Teknologi MARA, Perak, 2021)
In both Malaysia and Indonesia, traditional houses have been used as homestays, as a new type of rural tourism accommodation. This study aims to compare the implementation of rural tourism in Malaysia and Indonesia, to reveal the usage of traditional Malay house and Rumah Gadang as homestays in both countries, and to promote homestay as an alternative for rural tourism accommodation. Experiences on participating in both homestays in Kampung Lonek Homestay, Negeri Sembilan, Malaysia and Nagari Sumpur, West Sumatra, both majorly populated by the Minang community, are shared and analyzed to achieve these aims.